Effect of Process Temperature on Nickel Powder Production using Electrodeposition Method in NiSO4-NiCl2-H3BO3 Solution - Wahyuningsih, Tri; Sudiyanto, Anton; Sudaryanto, Sudaryanto; Samuel, Reinhart; Kalimasawa, Rajadwa; Mawarda, Mei Iftita; Pujiyulianto, Eko (RSF Conference Series: Engineering and Technology, 2022)
This paper aims to know the effect of process temperature on nickel powder production using the electrodeposition method in 500 ml of NiSO4-NiCl2-H3BO3 solution. The temperatures that were varied were 27?C, 40?C, and 50?C. The processing time was 15 minutes, and the current density was 2.2 A. The difference in the effect of temperature will be explained by the weight of the metal powder produced in the electrodeposition process. The powder results were then analyzed using an optical microscope, and the experiment that produced the highest powder weight would be further analyzed using a Scanning Electron Microscope (SEM) to characterize the morphology and grain size of nickel powder. The chemical composition was analyzed using Energy Dispersive X-Ray (EDX). The results show that the weight of nickel powder after electrodeposition is 0.58 g, 0.49 g, and 0.46 g for 27?C, 40?C, and 50?C, respectively. The most weights of nickel powder is produced from 27?C. The powder that is produced at 27oC has a smaller size and is uniform. The morphology of nickel powder is irregular with an average powder size range is 1-5 ?m. The higher current efficiency occurs at 27oC with the current density of 2.4 A/dm2